2017
DOI: 10.1038/s41598-017-06152-9
|View full text |Cite
|
Sign up to set email alerts
|

The sex ratio of singleton and twin delivery offspring in assisted reproductive technology in China

Abstract: In order to evaluate the impact of assisted reproductive technology (ART) procedure and individual factors on the sex ratio of singletons and twins at birth after in vitro fertilization (IVF) and intra-cytoplasmic sperm injection (ICSI) treatment in China. We conducted a retrospective cohort study including patients undergoing their first cycle of IVF or ICSI with autologous oocytes from 2001 to 2015. A total of 7410 babies were born from 5832 women with 7410 live birth. The secondary sex ratio (SSR) in single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Some researchers specifically used systematic review to clarify that blastocyst stage transplantation might increase the SSR when it was compared with cleavage stage transplantation [ 4 6 ]. Other aspects, single or multiple births might also have an influence on the SSR [ 7 ]. In addition to this, paternal age, maternal age, smoking, even stress were the influencing factors of SSR [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers specifically used systematic review to clarify that blastocyst stage transplantation might increase the SSR when it was compared with cleavage stage transplantation [ 4 6 ]. Other aspects, single or multiple births might also have an influence on the SSR [ 7 ]. In addition to this, paternal age, maternal age, smoking, even stress were the influencing factors of SSR [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Another Chinese study reported more male babies after IVF ( n = 5381) compared with ICSI (n = 1111), but the difference was not statistically significant (53.2% vs 50.4%, respectively; P = .10). [ 2 ] Data from a UK national registry of over 100,000 babies also noted significantly more male babies after IVF compared with ICSI (52.1% vs 49.3%, respectively; P < .0001). [ 3 ] A small study of 38 monozygotic twins reported a 2.2 male:female sex ratio following IVF compared with a 0.58 ratio following ICSI (69.0% vs 36.8% male babies, respectively; P = .004).…”
Section: Discussionmentioning
confidence: 99%
“…With few exceptions, studies support an increase in male babies following blastocyst transfer compared with cleavage-stage embryos, and following in vitro fertilization (IVF) compared with intracytoplasmic sperm injection (ICSI). [ 2 , 3 ] However, data from patients’ specific sociodemographic environments can be more meaningful, when answering patient questions regarding ART and sex. Accordingly, we examined outcomes for ART procedures performed in 2015 at our tertiary referral center, the Reproductive Endocrine and Infertility Medicine Department at King Fahad Medical City, Riyadh, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…As consequence, more and more infertility women are seeking for treatment, assisted reproductive technology (ART) has become an important option for patients with infertility who wish to become pregnant and contributed to the birth of over 5 million live born babies worldwide [12,13]. Over the past decades, with the rapid popularity of ART for infertility treatment, a growing number of babies were born from in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) [14]. Controlled ovarian hyper-stimulation (COH) is a fundamental part and the key to the success and safety of ART, while the gonadotropinreleasing hormone agonist (GnRH-a) long protocol is one of the common regimens for ovarian stimulation [15].…”
Section: Introductionmentioning
confidence: 99%